2018
DOI: 10.1124/mol.117.111039
|View full text |Cite
|
Sign up to set email alerts
|

CYP26C1 Is a Hydroxylase of Multiple Active Retinoids and Interacts with Cellular Retinoic Acid Binding Proteins

Abstract: The clearance of retinoic acid (RA) and its metabolites is believed to be regulated by the CYP26 enzymes, but the specific roles of CYP26A1, CYP26B1, and CYP26C1 in clearing active vitamin A metabolites have not been defined. The goal of this study was to establish the substrate specificity of CYP26C1, and determine whether CYP26C1 interacts with cellular retinoic acid binding proteins (CRABPs). CYP26C1 was found to effectively metabolize all- retinoic acid (RA), 9--retinoic acid (9--RA), 13--retinoic acid, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…The reactions catalyzed (Fig. 23) are similar as for P450 26B1, although recent work by Zhong et al (2018) has defined some important differences in both the substrate and product profiles. Zhong et al (2018) reported that P450 26C1 has a specificty constant ( k cat / K m ) up to 10-fold higher than P450 26A1 or 26B1 in oxidizing all- trans -4-oxo retinoic acid.…”
Section: Retinoid Metabolismmentioning
confidence: 73%
“…The reactions catalyzed (Fig. 23) are similar as for P450 26B1, although recent work by Zhong et al (2018) has defined some important differences in both the substrate and product profiles. Zhong et al (2018) reported that P450 26C1 has a specificty constant ( k cat / K m ) up to 10-fold higher than P450 26A1 or 26B1 in oxidizing all- trans -4-oxo retinoic acid.…”
Section: Retinoid Metabolismmentioning
confidence: 73%
“…CYP26C1 also cleared RA metabolite 4-oxo-atRA more efficiently than the other two CYP26 enzymes. Overall, the metabolisation of RA by the CYP26 enzymes is up to 10 4 -fold higher than for other CYP enzymes shown to hydroxylate RA in the liver, such as CYP3A4, CYP3A5, CYP3A7, CYP2C8 and CYP2C22 [135,[137][138][139][140][141][142][143][144][145][146][147][148][149][150].…”
Section: Cyp26 Structure Biochemistry and Functionmentioning
confidence: 90%
“…These are thought to be produced from the β-ionone ring of RA following multiple hydroxylations. These chemical forms are less biologically active than RA and undergo further glucuronation by UDP-glucuronosyltransferases (e.g., UTP2B7) to 4-O-β-glucuronide and are eventually eliminated from the cell (Figure 1) [139,143,144,146,[150][151][152].…”
Section: Cyp26 Structure Biochemistry and Functionmentioning
confidence: 99%
“…In zebrafish, however, the expression of zebrafish crabp2a and crabp2b is essential for hindbrain development and to ensure the robustness of RA-based patterning (Cai et al, 2012;Rackauckas, Schilling, & Nie, 2018;Schilling et al, 2012). Recent studies have revealed that both holo-CRABP1 and holo-CRABP2 deliver RA to CYP26B1 or CYP26C1 (Nelson et al, 2016;Zhong, Ortiz, Zelter, Nath, & Isoherranen, 2018). CRABP2 has been proposed to deliver RA to the nucleus for signaling while CRABP1 has been proposed to sequester RA and target it for degradation by CYP26 enzymes (Fiorella & Napoli, 1994).…”
Section: Regulation Of Ra Synthesis and Catabolismmentioning
confidence: 99%
“…CRABP2 has been proposed to deliver RA to the nucleus for signaling while CRABP1 has been proposed to sequester RA and target it for degradation by CYP26 enzymes (Fiorella & Napoli, 1994). Recent studies have revealed that both holo-CRABP1 and holo-CRABP2 deliver RA to CYP26B1 or CYP26C1 (Nelson et al, 2016;Zhong, Ortiz, Zelter, Nath, & Isoherranen, 2018). Meanwhile, unliganded apo-CRABPs inhibited the metabolism of RA by CYP26B1.…”
Section: Regulation Of Ra Synthesis and Catabolismmentioning
confidence: 99%